Voluntourism and the contract corrective. Issue 8 (3rd August 2018) - Banki, Susan; Schonell, Richard
Abstract: Critiques of the voluntourism industry focus on power imbalances, colonial legacies and white privilege. Drawing on the literatures of development and voluntourism to find points of comparison, we argue that the voluntourism industry reflects myriad development problems, such as structural challenges, the fungibility of aid, corruption, representation, worker narratives and temporality. We assert that many of the problems inherent in voluntourism could be remedied by the evolution of a contract norm between volunteers and their local partners, where reciprocity and transparency might practically serve as a corrective to voluntourism's most entrenched problems.